2020
DOI: 10.3389/fpsyg.2020.01214
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated With Negotiation Effectiveness: The Role of Mindfulness

Abstract: Negotiation is the main mean of conflict resolution. Despite its capital importance, little is known about influencing variables or effective interventions. Mindfulness has shown to improve subjects' performance in different settings but until now, no study has shown its impact in negotiation. The aim of this study is to analyze which variables are associated with effectiveness and to determine if meditators are more effective in negotiation. A cross-sectional descriptive study was carried out. The study varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…In complex violent situations, patients’ reasoning about conflicts varies from different domains that impacts their use, or lack of use, of violence in that particular situation. Among five different conflict management styles, compromising and integrating are the two most effective conflict management styles [ 61 , 62 , 63 ]. However, the integrating solution is generally hard to come by.…”
Section: Discussionmentioning
confidence: 99%
“…In complex violent situations, patients’ reasoning about conflicts varies from different domains that impacts their use, or lack of use, of violence in that particular situation. Among five different conflict management styles, compromising and integrating are the two most effective conflict management styles [ 61 , 62 , 63 ]. However, the integrating solution is generally hard to come by.…”
Section: Discussionmentioning
confidence: 99%
“…This model includes five personality traits, i.e., 'openness to experience', 'neuroticism', 'conscientiousness', 'agreeableness' and 'extraversion'. The long version of the scale -used in this study-showed high internal consistency and a reproducibility of its five-factor structure (Pérez-Yus et al 2020). The next section describes these five dimensions and their relationship to perceptions of unethical conduct.…”
Section: Personality Traitsmentioning
confidence: 92%
“…It is widely recognized as a key component in determining strategic choices and outcomes of negotiation (Ahmed et al 2010). Despite the body of knowledge on personality traits in the business negotiation context (de Moura and Costa 2018;Dimotakis, Conlon and Ilies 2012;Ma 2008;Ome 2013;Pérez-Yus et al 2020;Sharma, Bottom and Elfenbein 2013;Spain et al 2014;Spain, Harms and LeBreton 2014;Wilson et al 2016), many areas of research have not been covered and the studies are still specific to some contexts and cultures (Ma and Jaeger 2005).…”
Section: Personality Traitsmentioning
confidence: 99%
“…Negotiation styles have been linked to negotiation effectiveness. The most effective negotiation style combines compromising, integrating, and dominating styles [6]. Negotiators who possess a high level of emotional intelligence (EI) are capable of acquiring a broader and more comprehensive array of information regarding their opponent's essential interests, accurately gauging risks, employing strategies that involve managing their own emotions or the emotions of their counterparts, and evoking desirable emotions in those counterparts.…”
Section: Negotiation Effectivenessmentioning
confidence: 99%